The palimpsest of the house (İstanbul)
vii, 292 sayfa
Keywords: “Material remains of houses and textual evidence for private living are crucial to our understanding of the architectural and decorative characteristics of the ancient house and the way private space was used. As buildings in which a range of activities could take place, ancient houses constitute an indispensable source for understanding social, economic, political, and religious aspects of past societies. However, despite their invaluable significance for our knowledge of ancient times, they remain a largely underappreciated research field. This volume intends to add a contribution to housing studies by using a broad diachronic and transcultural approach that addresses Roman, Late Antique, Byzantine, and the Early Islamic periods. The contributions are based on papers presented at the 8th International ANAMED Annual Symposium The Palimpsest of the House: Re-Assessing Roman, Late Antique, Byzantine, Early Islamic Living Patterns (Koç University Research Center for Anatolian Civilizations in Istanbul, 2013). The volume focuses on the developments, continuities, changes, and exchanges private housing across the Mediterranean underwent in these time periods, giving ancient Constantinople, the venue of the symposium, special attention. All contributions present up-to-date results and interpretations of field and research projects as well as new readings of literary and epigraphical evidence. Of the multiple perspectives that can be explored when studying ancient housing, this volume opts for a diachronic and interregional approach prioritizing a focus on the architectural remains of urban, suburban, and rural upper-class houses, which due to their often century-long occupation allow retracing different building and occupation layers and thus to study them as “palimpsests.” By considering a broad time frame and utilizing a cross-cultural viewpoint, the volume intends to reflect on transitional periods and the impact of historical events and investigates patterns of networks, encounters, and (mutual) exchanges“ -- Yayıncı.